Prosthetic Joint Infections (Springer International Publishing, 2018)
This book outlines the most updated clinical guidelines that are vital for the prevention infections and care of patients with joint infections following a replacement surgery, one of the highest volume medical interventions globally. Sections address the diagnosis, management approaches and prevention of prosthetic joint infections. Written by experts in the field, this text provides a brief overview of the literature and current recommendations in each of the specified areas. Given the rapidly evolving state-of-play in this clinical area, this compendium grows increasingly important to clinicians in their management decisions. Prosthetic Joint Infections is a valuable resource for infectious disease specialists, epidemiologists, surgeons, and orthopedic specialists who may work with patients with prosthetic joint infections.